Nanometer magnetic particle and preparation method and application thereof
By preparing nanomagnetic particles, using the chemical composition and nanocrystalline structure of Sr1-x-yBaxLayFe12-zCozO19, the problem of low magnetic performance of existing hexagonal ferrite permanent magnet materials is solved, and high magnetic storage density is achieved to meet the data storage needs in the information age.
Patent Information
- Application Number
- CN202311089929.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-02-28
AI Technical Summary
The existing hexagonal ferrite permanent magnet materials have low magnetic performance in magnetic storage devices, resulting in insufficient magnetic storage density and cannot meet the storage needs of huge data in the information age.
Using the preparation method of nanomagnetic particles, by using Sr1-x-yBaxLayFe12-zCozO19 as a chemical component, the average particle size of the particles is controlled to form nanocrystalline structure to improve magnetic properties.
It has achieved excellent magnetic properties of nanomagnetic particles, with saturated magnetic induction strength (Ms) up to 77.3emu/g, residual magnetization strength (Mr) up to 45.1emu/g, and coercive force (Hcj) up to 4.15kOe, meeting the high record density requirements of magnetic storage devices.
Smart Images

Figure BDA0004417378510000091 
Figure BDA0004417378510000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic materials and relates to nano magnetic particles and a preparation method and application thereof. Background Art
[0002] In recent years, as magnetic recording devices have been developing towards higher-density recording, higher and higher requirements have been placed on the magnetic properties of magnetic materials.
[0003] Although the magnetic properties of hexagonal ferrite permanent magnet materials are not as good as those of rare earth permanent magnets, they have many advantages such as abundant resources, simple preparation process, and low material cost. They are widely used in motors, sensors, magnetic storage and other fields, and are currently the largest type of permanent magnet materials. When hexagonal ferrite permanent magnet materials are used in magnetic storage devices, they are particularly suitable for magnetic storage devices that need to be stored for a long time due to their resistance to high temperatures, corrosion and oxidation. In the current information and data era, there is a large amount of "warm data" and "cold data" that need to be stored for a long time, so hexagonal ferrite magnetic storage media have attracted widespread attention.
[0004] CN102076629A discloses a reinforced hexagonal ferrite magnetic material, in which alkali metal is doped.
[0005] CN109836147A discloses a permanent ferrite and a preparation method thereof. Based on the total mass of the permanent ferrite, the permanent ferrite is composed of 55wt% or more of Sr-based ferrite material and 45wt% or less of Ca-based ferrite material; the Sr-based ferrite material has Sr 1-x La x Fe 3+ 2n-y Co y O 19 Ferrite main phase; the Ca-based ferrite material has Ca x (Sr+Ba) y La 1-x-y Fe 3+ 2n-z Co z O 19 Ferrite main phase.
[0006] The ferrite material described in the above scheme has large particle size and poor magnetic properties. Due to the low magnetic properties of ferrite materials, its magnetic storage density is relatively small, which cannot meet the storage needs of huge data in the information age, and has become a key bottleneck restricting its widespread application. Summary of the invention
[0007] The purpose of the present invention is to provide a nanomagnetic particle and a preparation method and application thereof. The nanomagnetic particle of the present invention has a small particle size and exhibits excellent magnetic properties. The use of the nanomagnetic particle in a magnetic storage device can further meet the storage needs of huge data in the information age.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a nanomagnetic particle, wherein the chemical formula of the nanomagnetic particle is Sr 1-x- y Ba x La y Fe 12-z Co z O 19 , wherein 0≤x≤0.3, 0≤y≤0.3, 0≤z≤0.25, x, y and z are not 0 at the same time, and the average particle size of the nanomagnetic particles is 20-40 nm, for example: 20 nm, 25 nm, 30 nm, 35 nm or 40 nm.
[0010] The nano-magnetic particles of the present invention have a nano-crystalline structure (average particle size is less than 50nm), and the nano-crystalline structure makes the coercivity of the material increase as the grain size decreases. In particular, when the grain size is less than 50nm, a strong exchange coupling effect will occur between adjacent grains, greatly improving the remanence of the material. At the same time, the magnetic particles have Sr 1-x- y Ba x La y Fe 12-z Co z O 19 Its chemical composition has excellent magnetic properties, making it more suitable for the development of high recording density magnetic storage devices.
[0011] Preferably, among the nanomagnetic particles, particles with a particle size of 10 to 40 nm (for example, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm or 40 nm, etc.) account for ≥90%.
[0012] Preferably, among the nanomagnetic particles, the proportion of particles with a particle size >40 nm (for example, 40.5 nm, 41 nm, 43 nm, 45 nm, 48 nm or 49 nm, etc.) is ≤5%, for example, 1%, 2%, 3%, 4% or 5%, etc.
[0013] Preferably, among the nanomagnetic particles, particles with a particle size of <10 nm (for example, 9 nm, 8 nm, 7 nm, 6 nm, 5 nm or 3 nm, etc.) account for ≤5%, for example, 1%, 2%, 3%, 4% or 5%, etc.
[0014] Among the nanomagnetic particles of the present invention, the sum of particles with a particle size of 10-40nm, a particle size >40nm and a particle size <10nm is 100%. For example, particles with a particle size of 10-40nm account for 95%, particles with a particle size >40nm account for 3%, and particles with a particle size <10nm account for 2%.
[0015] Preferably, when both y and z are not 0, y and z satisfy the relationship: 1≤y / z≤1.5, for example: 1, 1.1, 1.2, 1.36, 1.4 or 1.5, etc.
[0016] In a second aspect, the present invention provides a method for preparing the nanomagnetic particles according to the first aspect, the preparation method comprising the following steps:
[0017] (1) Main material A and main material B are mixed in proportion to obtain a mixed material, wherein main material A includes SrCO3 and Fe2O3, and main material B includes any one or a combination of at least two of BaCO3, La2O3 or Co2O3, and the mixed material is mixed with H3BO3 and SrCl2, ground and then calcined;
[0018] (2) melting the calcined material and flowing it onto a water-cooled roller to obtain an amorphous sheet;
[0019] (3) After heating and crystallizing the amorphous thin slice, washing is performed to obtain the nanomagnetic particles.
[0020] In the preparation process of nano magnetic particles of the present invention, H3BO3 and SrCl2 are added to promote the melting of the mixture and adjust the viscosity of the melt, thereby affecting the thickness of the amorphous sheet and its cooling speed on the roller, and finally affecting the microstructure and performance of the material.
[0021] Preferably, the mass of the H3BO3 in step (1) is 15-25% of the mass of the mixed material, for example: 15%, 18%, 20%, 22% or 25%, etc.
[0022] Preferably, the mass of the SrCl2 is 10-20% of the mass of the mixed material, for example: 10%, 12%, 15%, 18% or 20%, etc.
[0023] Preferably, the grinding method in step (1) comprises ball milling.
[0024] Preferably, the calcination temperature is 900-1100°C, for example, 900°C, 950°C, 1000°C, 1050°C or 1100°C.
[0025] Preferably, the calcination treatment time is 1 to 3 hours, for example: 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours.
[0026] The purpose of the calcination treatment of the present invention is to make the elements diffuse mutually in the solid state, so as to avoid the uneven distribution of the material after melting due to inconsistent density in the subsequent melting process, resulting in the segregation of elemental components caused by insufficient diffusion of atoms.
[0027] Preferably, the temperature of the melt treatment in step (2) is 1350-1500°C, for example: 1350°C, 1380°C, 1400°C, 1450°C or 1500°C.
[0028] Preferably, the outflowing specifically comprises pouring the melted liquid into a tubular container with a nozzle, and simultaneously introducing air to wet-press the liquid so that the liquid flows out through the nozzle.
[0029] Preferably, the rotation speed of the water-cooled roller is 20-30 m / s, for example, 20 m / s, 22 m / s, 25 m / s, 28 m / s or 30 m / s.
[0030] Preferably, the temperature of the heating crystallization treatment in step (3) is 550-650°C, for example, 550°C, 580°C, 600°C, 620°C or 650°C.
[0031] The present invention can adjust the size of crystal grains and particles by controlling the crystallization temperature and time. If the temperature is too low, the crystal grain size is too small, resulting in too many paramagnetic particles, and may also cause the same particle to contain multiple tiny crystal grains, making the material a polycrystalline structure. If the temperature is too high, the material grains will grow excessively, the particles will be too coarse and affect the magnetic properties.
[0032] Preferably, the heating crystallization time is 4 to 6 hours, for example: 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.
[0033] Preferably, the washing treatment in step (3) comprises placing the material obtained after heating and crystallization in water, adding acid to dissolve it repeatedly until all non-magnetic materials in the material are dissolved and washed away, precipitating the remaining material, and repeatedly washing it with alcohol.
[0034] Preferably, the washing is followed by a drying process.
[0035] Preferably, the drying treatment temperature is 100-110°C, for example, 100°C, 102°C, 105°C, 108°C or 110°C.
[0036] In a third aspect, the present invention provides a use of the nanomagnetic particles as described in the first aspect, wherein the nanomagnetic particles are used in a magnetic storage device.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) In the preparation process of nanomagnetic particles of the present invention, H3BO3 and SrCl2 are added to promote the melting of the mixture and adjust the viscosity of the melt, thereby affecting the thickness of the amorphous sheet and its cooling rate on the roller, and ultimately affecting the microstructure and performance of the material.
[0039] (2) The nanomagnetic particles of the present invention have a nanocrystalline structure (average particle size is less than 50nm). The nanocrystalline structure increases the coercivity of the material as the grain size decreases. In particular, when the grain size is less than 50nm, a strong exchange coupling effect will occur between adjacent grains, greatly improving the remanence of the material. At the same time, the magnetic particles have Sr 1-x- y Ba x La y Fe 12-z Co z O 19 Its chemical composition has excellent magnetic properties, making it more suitable for the development of high recording density magnetic storage devices.
[0040] (3) The nanomagnetic particles of the present invention can have Ms of more than 77.3emu / g, Mr of more than 45.1emu / g, and Hcj of more than 4.15kOe while ensuring an average particle size of less than 30nm, showing good magnetic properties. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0042] Example 1
[0043] This embodiment provides a nanomagnetic particle, and the preparation method of the nanomagnetic particle is as follows:
[0044] (1) SrCO3, BaCO3, La2O3, Fe2O3, and Co2O3 are mixed in proportion so that the atomic ratio of each element satisfies Sr 1-x-y Ba x La y Fe 12-z Co z O 19, where x=0, y=0.3, z=0.25, y / z=1.2, then add 25% of the total weight of the mixture H3BO3 and 10% of SrCl2, put the mixture into a ball mill, add deionized water and ball mill for 5 hours, where the weight ratio of material, ball and water is 1:10:1.5, pour the mixed material together with the solution into a container, then heat and dry at 110°C, put the dried powder into a muffle furnace and calcine for 2 hours at a calcination temperature of 1000°C;
[0045] (2) The calcined product is placed in a crucible, heated to 1400°C to melt, and then poured into a tubular container with a nozzle, and air is introduced to wet press the liquid so that it flows through the nozzle onto a water-cooled roller rotating at a high speed (25 m / s), thereby obtaining a thin sheet with an amorphous microstructure;
[0046] (3) The amorphous thin slice is heated at 600°C for 5 hours for crystallization, and the crystallized thin slice is put into water and repeatedly dissolved with hydrochloric acid until the residual non-magnetic SrO, BaO, La2O3, Fe2O3, Co2O3, H3BO3 and SrCl2 in the thin slice are completely dissolved and washed away, and the remaining product is precipitated, and repeatedly washed with alcohol, and then dried at 110°C to obtain the nanomagnetic particles. The average particle size of the magnetic powder is 23nm, of which particles with a size of 10 to 40nm account for 95%, particles with a particle size of >40nm account for 2%, and particles with a particle size of <10nm account for 3%.
[0047] Example 2
[0048] This embodiment provides a nanomagnetic particle, and the preparation method of the nanomagnetic particle is as follows:
[0049] (1) SrCO3, BaCO3, La2O3, Fe2O3, and Co2O3 are mixed in proportion so that the atomic ratio of each element satisfies Sr 1-x-y Ba x La y Fe 12-z Co z O 19 , where x=0, y=0.3, z=0.25, y / z=1.2, then add 15% of the total weight of the mixture H3BO3 and 20% of SrCl2, put the mixture into a ball mill, add deionized water and ball mill for 5 hours, where the weight ratio of material, ball and water is 1:10:1.5, pour the mixed material together with the solution into a container, then heat and dry at 110°C, put the dried powder into a muffle furnace and calcine for 3 hours at a calcination temperature of 900°C;
[0050] (2) The calcined product is placed in a crucible, heated to 1350°C to melt, and then poured into a tubular container with a nozzle, and air is introduced to wet press the liquid so that it flows through the nozzle onto a water-cooled roller rotating at a high speed (20 m / s), thereby obtaining a thin sheet with an amorphous microstructure;
[0051] (3) The amorphous thin slice is heated at 550°C for 6 hours for crystallization, and the crystallized thin slice is put into water and repeatedly dissolved with hydrochloric acid until the residual non-magnetic SrO, BaO, La2O3, Fe2O3, Co2O3, H3BO3 and SrCl2 in the thin slice are completely dissolved and washed away, and the remaining product is precipitated, and repeatedly washed with alcohol, and then dried at 110°C to obtain the nanomagnetic particles. The average particle size of the magnetic powder is 28nm, of which particles with a size of 10 to 40nm account for 93%, particles with a particle size of >40nm account for 3%, and particles with a particle size of <10nm account for 4%.
[0052] Example 3
[0053] This embodiment provides a nanomagnetic particle, and the preparation method of the nanomagnetic particle is as follows:
[0054] (1) SrCO3, BaCO3, La2O3, Fe2O3, and Co2O3 are mixed in proportion so that the atomic ratio of each element satisfies Sr 1-x-y Ba x La y Fe 12-z Co z O 19 , where x=0, y=0.3, z=0.2, y / z=1.5, then add 15% of the total weight of the mixture H3BO3 and 10% of SrCl2, put the mixture into a ball mill, add deionized water and ball mill for 5 hours, where the weight ratio of material, ball and water is 1:10:1.5, pour the mixed material together with the solution into a container, then heat and dry at 110°C, put the dried powder into a muffle furnace and calcine for 1 hour, the calcination temperature is 1100°C;
[0055] (2) The calcined product is placed in a crucible, heated to 1500°C to melt, and then poured into a tubular container with a nozzle. Air is introduced into the container to wet-press the liquid, so that the liquid flows through the nozzle onto a water-cooled roller rotating at a high speed (30 m / s), thereby obtaining a thin sheet with an amorphous microstructure.
[0056] (3) The amorphous thin slice is heated at 650°C for 4 hours for crystallization, and the crystallized thin slice is put into water and repeatedly dissolved with hydrochloric acid until the residual non-magnetic SrO, BaO, La2O3, Fe2O3, Co2O3, H3BO3 and SrCl2 in the thin slice are completely dissolved and washed away, and the remaining product is precipitated, and repeatedly washed with alcohol, and then dried at 110°C to obtain the nanomagnetic particles. The average particle size of the magnetic powder is 23nm, of which particles with a size of 10 to 40nm account for 96%, particles with a particle size of >40nm account for 2%, and particles with a particle size of <10nm account for 2%.
[0057] Example 4
[0058] The only difference between this embodiment and embodiment 1 is that the amount of H3BO3 added is 10% of the mixture, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0059] Example 5
[0060] The only difference between this embodiment and embodiment 1 is that the amount of H3BO3 added is 30% of the mixture, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0061] Example 6
[0062] The only difference between this embodiment and embodiment 1 is that the amount of SrCl2 added is 5% of the mixture, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0063] Example 7
[0064] The only difference between this embodiment and embodiment 1 is that the amount of SrCl2 added is 25% of the mixture, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0065] Comparative Example 1
[0066] (1) SrCO3, BaCO3, La2O3, Fe2O3, and Co2O3 are mixed in proportion so that the atomic ratio of each element satisfies Sr 1-x-y Ba x La y Fe 12-z Co z O 19 , where x=0, y=0.3, z=0.25, y / z=1.2, then add 15% of the total weight of the mixture H3BO3 and 20% of SrCl2, put the mixture into a ball mill, add deionized water and ball mill for 5 hours, where the weight ratio of material, ball and water is 1:10:1.5, pour the mixed material together with the solution into a container, then heat and dry at 110°C, put the dried powder into a muffle furnace and calcine for 3 hours at a calcination temperature of 900°C;
[0067] (2) The calcined material is put into water, and hydrochloric acid is added to dissolve repeatedly until the residual non-magnetic SrO, BaO, La2O3, Fe2O3, Co2O3, H3BO3 and SrCl2 in the material are completely dissolved and washed away, and the remaining product is precipitated, and repeatedly washed with alcohol, and then dried at 110°C to obtain ferrite magnetic powder particles. The average particle size of the magnetic powder is 0.9 μm, which is much larger than the magnetic powder particle size in the embodiment.
[0068] Comparative Example 2
[0069] The only difference between this comparative example and Example 1 is that SrCl2 is not added, and the other conditions and parameters are exactly the same as those in Example 1.
[0070] Comparative Example 3
[0071] The only difference between this comparative example and Example 1 is that x=0, y=0, z=0, and the other conditions and parameters are exactly the same as those in Example 1.
[0072] Performance Test:
[0073] The magnetic materials obtained in the embodiment and the comparative example were tested by VSM analysis for saturation magnetic induction intensity Ms, residual magnetization intensity Mr and coercive force Hcj, and the test results are shown in Table 1:
[0074] Table 1
[0075]
[0076]
[0077] As can be seen from Table 1, from Examples 1-3, the nanomagnetic particles of the present invention can achieve Ms of more than 77.3emu / g, Mr of more than 45.1emu / g, and Hcj of more than 4.15kOe while ensuring an average particle size of less than 30nm, showing good magnetic properties.
[0078] By comparing Example 1 with Examples 4-5, it can be seen that in the preparation process of the nanomagnetic particles of the present invention, the amount of H3BO3 added will affect its performance. When the amount of H3BO3 added is controlled at 15-25% of the mass of the mixture, the performance of the obtained magnetic nanoparticles is better. If the amount of boric acid added is too low, the melt viscosity is high, and the dispersibility on the roller is poor, resulting in unreasonable particle size distribution, Ms, Mr and Hcj are all low. If the amount of boric acid added is too high, the melt viscosity is low, the paramagnetic particles smaller than 10nm in the magnetic powder are more, and Ms, Mr and Hcj are also not ideal.
[0079] By comparing Example 1 with Examples 6-7, it can be seen that in the preparation process of the nanomagnetic particles of the present invention, the amount of SrCl2 added will affect its performance. When the amount of SrCl2 added is controlled at 10-20% of the mass of the mixture, the performance of the obtained magnetic nanoparticles is better. If the amount of SrCl2 added is too low, although the particles have a better Hcj, the Ms and Mr are low. If the amount of SrCl2 added is too high, the Ms and Mr of the particles increase slightly, but the Hcj is low.
[0080] From the comparison between Example 1 and Comparative Example 1, it can be seen that the nanomagnetic particles of the present invention have a nanocrystalline structure (average particle size is less than 50nm). The nanocrystalline structure increases the coercivity of the material as the grain size decreases. In particular, when the grain size is less than 50nm, a strong exchange coupling effect will occur between adjacent grains, greatly improving the remanence of the material. At the same time, the magnetic particles have Sr 1-x-y Ba x La y Fe 12-z Co z O 19 Its chemical composition has excellent magnetic properties, making it more suitable for the development of high recording density magnetic storage devices.
[0081] By comparing Example 1 and Comparative Example 2, it can be seen that without adding SrCl2, the Ms, Mr and Hcj of the material will decrease.
[0082] By comparing Example 1 and Comparative Example 3, it can be seen that without adding Ba, La and Co to the nanomagnetic particles of the present invention, the Ms, Mr and Hcj of the material all decrease to varying degrees. Although the particle size is small, the magnetic properties are deteriorated and it is not suitable for high recording density of magnetic storage devices.
[0083] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A nano magnetic particle, characterized in that: The chemical formula of the nanomagnetic particles is Sr 1-x-y Ba x La y Fe 12- z Co z O 19 , wherein 0≤x≤0.3, 0≤y≤0.3, 0≤z≤0.25, x, y and z are not 0 at the same time, and the average particle size of the nanomagnetic particles is 20 to 40 nm.
2. The nanomagnetic particle according to claim 1, characterized in that Among the nanomagnetic particles, particles with a particle size of 10 to 40 nm account for ≥90%; Preferably, among the nanomagnetic particles, particles with a particle size of >40 nm account for ≤5%; Preferably, among the nanomagnetic particles, particles with a particle size of less than 10 nm account for ≤5%.
3. The nanomagnetic particle according to claim 1 or 2, characterized in that: When both y and z are not 0, y and z satisfy the relationship: 1≤y / z≤1.
5.
4. A method for preparing the nanomagnetic particles according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) Main material A and main material B are mixed in proportion to obtain a mixed material, wherein main material A includes SrCO3 and Fe2O3, and main material B includes any one or a combination of at least two of BaCO3, La2O3 or Co2O3, and the mixed material is mixed with H3BO3 and SrCl2, ground and then calcined; (2) melting the calcined material and flowing it onto a water-cooled roller to obtain an amorphous sheet; (3) After heating and crystallizing the amorphous thin slice, washing is performed to obtain the nanomagnetic particles.
5. The preparation method according to claim 4, characterized in that: The mass of H3BO3 in step (1) is 15-25% of the mass of the mixed material; Preferably, the mass of the SrCl2 is 10-20% of the mass of the mixed material.
6. The preparation method according to claim 4 or 5, characterized in that: The grinding method in step (1) includes ball milling; Preferably, the calcination temperature is 900-1100°C; Preferably, the calcination treatment time is 1 to 3 hours.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The temperature of the melting treatment in step (2) is 1350-1500° C. Preferably, the flowing out specifically comprises pouring the melted liquid into a tubular container with a nozzle, and simultaneously introducing air to wet-press the liquid so that the liquid flows out through the nozzle; Preferably, the rotation speed of the water-cooled roller is 20-30 m / s.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The temperature of the heating crystallization treatment in step (3) is 550-650°C; Preferably, the heating crystallization time is 4 to 6 hours.
9. The preparation method according to any one of claims 4 to 8, characterized in that: The washing treatment in step (3) comprises placing the material obtained after heating and crystallization in water, adding acid and repeatedly dissolving it until all non-magnetic materials in the material are dissolved and washed away, precipitating the remaining material, and repeatedly washing it with alcohol; Preferably, the washing is followed by drying; Preferably, the drying temperature is 100-110°C.
10. A use of the nanomagnetic particles according to any one of claims 1 to 3, characterized in that: The nano magnetic particles are used in magnetic storage devices.
Citation Information
Patent Citations
Enhanced hexagonal ferrite material and methods of preparation and use thereof
CN102076629A
Permanent magnetic ferrite and preparation method thereof
CN109836147A